Cognitive Linguistics : Convergence and Expansion. - Brdar, Mario; Gries, Stefan Th; Zic Fuchs, Milena (Human cognitive processing, 2011)
Cognitive Linguistics is not a unified theory of language but rather a set of flexible and mutually compatible theoretical frameworks. Whether these frameworks can or should stabilize into a unified theory is open to debate. One set of contributions to the volume focuses on evidence that strengthens the basic tenets of CL concerning e.g. non-modularity, meaning, and embodiment. A second set of chapters explores the expansion of the general CL paradigm and the incorporation of theoretical insights from other disciplines and their methodologies - a development that could lead to competing and mutually exclusive theories within the CL paradigm itself. The authors are leading experts in cognitive grammar, cognitive pragmatics, metaphor and metonymy theory, quantitative corpus linguistics, functional linguistics, and cognitive psychology. This volume is therefore of great interest to scholars and students wishing to inform themselves about the current state and possible future developments of Cognitive Linguistics.